2018
DOI: 10.3389/fimmu.2018.01154
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils and Activated Macrophages Control Mucosal Immunity by Proteolytic Cleavage of Antileukoproteinase

Abstract: Antileukoproteinase or secretory leukocyte peptidase inhibitor is a small protein which protects the mucosal linings against excessive proteolysis, inflammation, and microbial infection. We discovered that gelatinase B or matrix metalloproteinase (MMP)-9, a secreted zinc-dependent endopeptidase typically found at sites of inflammation, destroys antileukoproteinase by cleavages within both of its two functional domains: the anti-microbial N-terminal and the anti-proteolytic C-terminal domains. Cleaved antileuko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 55 publications
2
10
0
Order By: Relevance
“…is is corroborated in the interaction network since homologs of this protein have strong interaction with proteins such as myeloperoxidase (score 0.755), which is microbicidal [53] and antileukoproteinase (score 0.969), a proteinase inhibitor that modulates the immune response after a bacterial infection [54]. is explains the fact that we found lactotransferrin with high abundance in cats' TF since the samples were from healthy animals.…”
Section: Discussionsupporting
confidence: 60%
“…is is corroborated in the interaction network since homologs of this protein have strong interaction with proteins such as myeloperoxidase (score 0.755), which is microbicidal [53] and antileukoproteinase (score 0.969), a proteinase inhibitor that modulates the immune response after a bacterial infection [54]. is explains the fact that we found lactotransferrin with high abundance in cats' TF since the samples were from healthy animals.…”
Section: Discussionsupporting
confidence: 60%
“…Importantly, we were able to demonstrate that processing of SLPI was directly related to increasing elastase activity. A number of studies have demonstrated protease inhibitor cleavage events in vitro that may be responsible for our findings; for example, SLPI is cleaved by cathepsins B, L, and S in COPD and by MMP9 and neutrophil elastase in cystic fibrosis (39,41,42). We (40) too have previously shown that MMP14 cleaves and inactivates SLPI.…”
Section: Discussionsupporting
confidence: 59%
“…The abundantly present protease inhibitors in the COVID-19 patient lungs could also be inactivated by proteolytic cleavage and still remain detectable by ELISA. For the protease inhibitor SLPI, it has been shown that MMP-9 and other neutrophil-derived proteases can cleave SLPI, resulting in a reduced capacity to inhibit neutrophil elastase activity ( 49 ).…”
Section: Discussionmentioning
confidence: 99%